Performance analysis of SiO₂PAG nanolubricant in automotive air conditioning system - M. Z., Sharif (2016)
Currently, the possibility to enhance fuel efficiency with cutting edge advancements is thoroughly investigated by researchers. One of the best ways to increase the fuel efficiency is by improving the performance of the automotive air conditioning (AAC) system. The AAC is currently a thing of necessity instead of just an accesory, and cooling is needed to give thermal comfort in the passenger’s cabin especially for countries like Malaysia, that experience hot weather throughout a year. With the hot weather climate and also because of the El-Nino impacts that occur frequently, the use of AAC in auto vehicles will increase drastically. This will affect the fuel consumption and consequently reduce the automobile travelling distance yearly. Therefore, the AAC performance needs to be enhanced in order to minimize its environmental impact and reduce global fuel consumption. The objectives of the present work are to formulate the SiO2/PAG nanolubricants and evaluate the thermal conductivity and viscosity of the nanolubricants. Furthermore, the AAC system test rig is designed and developed for performance analysis of SiO2/PAG nanolubricants in the system. The SiO2/PAG nanolubricant is formulated by the two-step method and had established the colloidal stability of the suspended nanoparticles. Then, the viscosity and thermal conductivity of the SiO2 nanoparticles dispersed in Polyalkylene glycol (PAG) lubricants for 0 to 1.5% volume concentrations and 30 to 80 °C working temperatures were investigated. The AAC experiment was conducted with initial refrigerant charge ranging from 95 to 125 gram and compressor speeds of 900 to 2100 rpm. The performance of the AAC system was evaluated by determining the heat absorb, compressor work and coefficient of performance (COP). The viscosity and thermal conductivity of the SiO2 nanolubricants increased with volume concentration but decreased with temperature. The thesis proposed correlations for viscosity and thermal conductivity of SiO2 nanolubricants at various concentrations and temperatures. From the thermo-physical properties evaluation, the use of SiO2/PAG nanolubricants for application in AAC compressor is applicable for volume concentrations up to 0.7% only. The overall AAC performance of the system improved and the compressor work related to the fuel consumption can be greatly reduced. The optimum refrigerant charge of the present AAC system run with PAG lubricant is attained with 115 g. The results found that the maximum increase and the average COP enhancement for SiO2/PAG nanolubricants are 24% and 10.5%, respectively. At 0.05% concentration, the system attained minimum compressor work with maximum COP. Consequently, it was observed that the COP was highest at 0.05% volume concentration for all compressor speeds. A volume concentration of 0.05% is found to be the best volume concentration for SiO2/PAG nanolubricants and dispersing SiO2 nanoparticle in PAG lubricant has proven to enhance the performance of the COP for all volume concentrations. Finally, it can be concluded that 0.05% is the optimum volume concentration of SiO2/PAG nanolubricants for applications in AAC systems. Therefore, it is recommended to use SiO2/PAG nanolubricants with a volume concentration of 0.05% for the best performance in the automotive air conditioning systems. This recommendation is supported by the visual investigation inside the mini channel of AAC evaporators which observed zero erosion and no clogging by the use of SiO2/PAG nanolubricants.